2022
DOI: 10.3389/fphar.2022.990799
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein prevents stress-induced anxiety behaviors in zebrafish model

Abstract: Baicalein is a flavonoid mainly obtained from plants with wide range of biological activities, including neuroprotection. An acute and unexpected chronic stress (UCS) protocol has recently been adapted to zebrafish, a popular vertebrate model in brain research. The present study was aimed to evaluate baicalein’s anti-anxiety potential in a zebrafish model by induction, which included neuropharmacological evaluation to determine behavioural parameters in the novel tank diving test (NTDT) and light-dark preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Polyphenolics and flavonoid compounds are found in almost every plant, including fruits, flowers, seeds, and vegetables. In rodent models, a variety of important flavonoids derived from fruits and plants have shown promising preclinical effects on emotional disorders such as stress and anxiety [ 49 ]. Zebrafish, a non-human animal, have advantages in modeling brain illnesses since they share behavioral features, genetic factors, and pharmacological sensitivity with rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenolics and flavonoid compounds are found in almost every plant, including fruits, flowers, seeds, and vegetables. In rodent models, a variety of important flavonoids derived from fruits and plants have shown promising preclinical effects on emotional disorders such as stress and anxiety [ 49 ]. Zebrafish, a non-human animal, have advantages in modeling brain illnesses since they share behavioral features, genetic factors, and pharmacological sensitivity with rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish are increasingly recognized as a promising model organism for anxiety and stress research due to their dependable and easily measurable cortisol stress response [58][59][60]. Zebrafish can experience acute stress upon exposure to air, changing water PH, salinity, temperature, crowding, handling, or exposure to bright light [13].…”
Section: Fear and Anxietymentioning
confidence: 99%
“…Moreover, zebrafish have been used as a model for anxiety in relation to different exposures [60,65,66]. Baicalein, a plant flavonoid, contributes to many biological processes, including neuroprotection [67].…”
Section: Fear and Anxietymentioning
confidence: 99%
“…Baicalein is a flavonoid isolated from Scutellaria lateriflora and Scutellaria balacalensis , has anti‐inflammatory, antioxidant, and anticancer effects 125 . Baicalein is regarded as an allosteric modulator of benzodiazepine receptors, and inhibits lipooxygenase 126 . It has been observed that baicalein has anticancer properties by numerous molecular mechanisms including inhibition of PI3K/AKT/mTOR, and MAPK 127 .…”
Section: Furin Inhibitorsmentioning
confidence: 99%
“… 125 Baicalein is regarded as an allosteric modulator of benzodiazepine receptors, and inhibits lipooxygenase. 126 It has been observed that baicalein has anticancer properties by numerous molecular mechanisms including inhibition of PI3K/AKT/mTOR, and MAPK. 127 Furthermore, baicalein inhibits adenosine diphosphate ribosylation factor 6, which promotes the proliferation and invasion of endometrial cancer cells.…”
Section: Furin Inhibitorsmentioning
confidence: 99%